KEMAMPUAN MEMBACA PEMAHAMAN LITERAL DAN INTERPRETATIF MELALUI PENDEKATAN KONSTRUKTIVISME - Sitti Fauziah Muis (Institut Agama Islam Negeri Kendari, 2013)
Abstrak: The results of reading literal and interpretatifunderstanding can be increased by using konstruktivisapproach. It can be seen on the process and the resultthat has been done. On the evaluating of reading literaland interpretatif understanding by using konstruktivismeapproach the students’ motivation is high, students’cooperation is active, self-learning is active, andstudents’ respond is very positive. On the evaluationprocess done by the students either cooperatively orindividually showed as the expected results.Kata kunci: peningkatan kemampuan, membaca literaldan interpretatif, pendekatan konstruktivisme